(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: ESBL-producing Enterobacteriaceae has become a prominent agent with high antibiotic resistance in pneumonia. Objectives: To determine characteristics of antibiotic resistance and genotypes of Enterobacteriaceae pneumonia. Method: We conducted this cross-sectional descriptive study on184 pneumonia patients caused by Enterobacteriaceae were treated at Thong Nhat Hospital from January 2020 to January 2022. Drug resistance genes detected by Multiplex Real-time PCR method. Results: Among 184 patients with pneumonia caused by Enterobacteriaceae, 97 cases of MDR and 87 cases of ESBL-producing agents accounted for 52.7% and 47.3%, respectively. In which ESBL Klebsiella pneumoniae and ESBL E.coli were 63.2%; 36.7%, respectively; MDR HAP and MDR CAP were 77.3% and 38.1%, respectively, a significant difference with p < 0.05. The percentage of antibiotic resistance in turn: ampicillin 98.9%, piperacillin/tazobactam 71%, ceftriaxon 95.3%; ceftazidime 83%; cefepime 75.8%, levofloxacin 90%; ciprofloxacin 91.7%; ertapenem 64.1%; imipenem 44.8%; meropenem 66.7%; amikacin 16.7%, colistin 7.7%. The ESBL-producing group was resistant to piperacillin/tazobactam 28.8%, ertapenem 27.8%, imipenem 10.6%, and meropenem 10%. The main drug resistance gene was SHV -231 (73.4%). The TEM-372 gene accounted for 50%, increasing the possibility of multidrug resistance with OR =3,74, 95%CI 1,31-10,61; p=0,013. No carbapenemase genotype was recorded. Conclusions: Enterobacteriaceae had a high rate of multidrug resistance (MDR). They were resistant to most antibiotics currently being used, except 28.8% to amikacin and 7.7% to colistin.. SHV-231 is a pronominal genotype of antibiotic resistance via Multiplex PCR. No carbapenemase genotype was recorded. Enterobactereacea strains carrying the TEM-372 gene increase the likelihood of multidrug resistance by 3.74 times.